Gambaran gangguan pendengaran pada bayi dengan hiperbilirubinemia di Rumah Sakit Umum Pusat. H. Adam Malik Medan - R. Yusa Herwanto; Abdul Hanum Rachman; T. Sofia Hanum (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introduction : Hearing function screening is usually performed on high risk infant of hyperbilirubinemia. According to Joint Committee of Infant Hearing, bilirubin level >17 mg/dl causing neurologic effect, especially on hearing function. To present the description of hearing disorder on infant with hyperbilirubinemia.Method : Descriptive study with case series design.Result : From 62 samples of hyperbilirubinemia infant on this research, 2 male samples (28.6 %) has bilirubin level >1.8 mg/dl and 5 female samples (71.4%) has bilirubin level >1.8 mg/dl. Based on group of age, samples on group of age '3d15 days with direct bilirubin level >1.8 gr/dl is two samples (28.6%), meanwhile on group of age >15 days with direct bilirubin level >1.8 mg/dl is five samples (71.4%). On group of age '3d15 days with total bilirubin level >17 gr/dl is nine samples (39.1%), and on group of age >15 days with total bilirubin level >17 gr/dl is 14 samples (60.9%). On right OAE with samples who has bilirubin level >1.8 mg/dl who declared pass is not found and who declared refer is 7 samples (100%). On left OAE with samples who has bilirubin level >1.8 mg/dl who declaredpass is not found and who declared refer is seven samples (100%). On Right OAE with samples who has total bilirubin level >17 mg/dl who declared pass is four samples (17.4%) and who declared refer is 19 samples (82.6%). On left OAE with samples who has total bilirubin level >17 mr/dl who declared pass is seven samples (30.4%), and who declared refer is 16 samples (69.6%).Conclusion : This research found 2 catageoris at bilirubin direct and total with left OAE refer have beenvalues (Bilirubin total P = 0.01 and Bilirubin direct P = 0.04) , it is means hearing disorder atinfant hyperbilirubinemia.Keywords : hearing disorder; hyperbilirubinemia of infant; OAE screenin